Relationship Between Gross Motor Function and Daily Functional Skill in Children With Cerebral Palsy - Kwon, Tae Gun (Korean Academy of Rehabilitation Medicine, 2013)
OBJECTIVE: To investigate the relationship between gross motor function and daily functional skill in children with cerebral palsy (CP) and to explore how this relationship is moderated by the Gross Motor Function Classification System, Bimanual Fine Motor Function (BFMF), neuromotor types, and limb distribution of CP. METHODS: A cross-sectional survey of 112 children with CP (range, 4 years to 7 years and 7 months) was performed. Gross motor function was assessed with the Gross Motor Function Measure-66 (GMFM-66) and functional skill was assessed with the Pediatric Evaluation of Disability Inventory-Functional Skills Scale (PEDI-FSS). RESULTS: GMFM-66 scores explained 49.7%, 67.4%, and 26.1% of variance in the PEDI-FSS scores in the self-care, mobility, and social function domains, respectively. Significant moderation by the distribution of palsy and BFMF classification levels II, III, and IV was found in the relationship between GMFM-66 and PEDI-FSS self-care. Further significant moderation by the distribution of palsy was also observable in the relationship between GMFM-66 and PEDI-FSS mobility. CONCLUSION: These findings suggest that limb distribution and hand function must be considered when evaluating gross motor function and functional skills in children with CP, especially in unilateral CP.